Designing A Children's Storybook at the A1 Level That Integrates Local Cultural Values Into Early Childhood Education - Putra, Ari; Dwi Lestari, Retno; Bin Bahurudin Setambah, Mohd Afifi; Boriboon, Gumpanat (UNIB Press, 2025)
The limited availability of reading materials that align with early childhood literacy development and are culturally contextual presents a significant challenge in educational processes rooted in local values. Most A1-level books currently in circulation do not adequately represent children's cultural experiences in their daily lives, thereby risking a disconnect between the world of reading and the child's reality. This study aims to design an initial prototype of an A1-level children's storybook that integrates local cultural values as an initial effort to provide educational, contextual, and culturally grounded literacy materials. A qualitative research approach was employed using the design-based research (DBR) method in its preliminary stage. It involved a needs assessment through curriculum document analysis, interviews with educators, and a review of local cultural literature as the basis for developing story scripts, selecting diction, and supporting illustrations. This phase resulted in a prototype design of a children's storybook featuring simple language structures, contextual illustrations, and narratives that highlight characters, traditions, and the child's surrounding cultural environment. The novelty of this research lies in the development of a literacy medium prototype that not only aims to enhance early childhood literacy skills but also intentionally integrates character-building values that are socio-culturally contextualized. This distinguishes the study from prior works, which predominantly focused on cognitive aspects of literacy without explicitly addressing the incorporation of character education and local cultural relevance. Thus, this research offers an innovative contribution by proposing a holistic and context-sensitive literacy learning medium, which can serve as a model for fostering literacy education that is attuned to the developmental needs of young children within the framework of local cultural values.